STUDY OF THE EFFECT OF AIR CONSUMPTION, LIQUID LAYER HEIGHT AND TEMPERATURE ON THE PROCESS OF FLOTATION SEPARATION OF GROUND PLASTICS - Apimakh Yauheni Vladimirovich; Leudanski Aliaksandr Eduardovich; Volnenko Alexandr Anatolevich; Zhumadullayev Daulet Koshkarovich (Academic Scientific Journal of Chemistry, 2020)
For separation of plastic wastes (polyamide (PA), acrylonitrile butadiene styrene (ABS) and polystyrene (PS)), a flotation method is proposed. Using this method, the effect of air consumption, liquid layer height and temperature were studied. As surface-active substances (surfactants), polidocanol, sulphanole and a mixture of surfactants containing sodium laureth sulfate and diethanolamide were used. To analyze the research results of flotation separation of a mixture of ground plastic wastes, the extraction of the floating component ε and the purity of the concentrate β were calculated. The research results on the extraction of polystyrene from the air consumption at various concentrations of a mixture of surfactants show that the extraction has a maximum at a certain air consumption. At low air consumption, the process is inefficient, since the working volume of the liquid is not saturated enough with gas bubbles. If the optimum value of air consumption is exceeded, many gas bubbles are formed that are not involved in the flotation process. Such bubbles, moving through a liquid, can create turbulent flows that impede flotation of particles. When moving in a turbulent liquid flow, the bubble-particle complex is prone to destruction, as particles and bubbles have different inertia (mass). In addition, it may be concluded that the air consumption value at which the maximum extraction of the floating component is achieved depends on the type of polymer and surfactant. The air consumption effect nature at different concentrations of surfactants is not changed – only the floating component extraction changes. The research results on the extraction of polystyrene from the aerated liquid layer height at various concentrations of a mixture of surfactants indicate that at a low height of the aerated liquid layer the probability of collision of a plastic particle with an air bubble is low and some potentially floating particles sink to the bottom of the device, without having time to collide with an air bubble. The optimum height of the processed liquid layer corresponds to a certain air consumption. When the liquid layer height is less than optimal, the achievement of the required extraction degree of the dispersed phase is possible, for example, with an increase in air consumption. When assessing the effect of liquid temperature on the flotation process, it was found that increasing the liquid temperature above 20°C leads to a sharp decrease in the ABS and PS extraction. This is possibly due to the fact that the dependence of the foaming capacity of surfactants on temperature is characterized by solubility curves and for most surfactants they have an extremum. Probably, an increase in the solution temperature leads to the dehydration of the dissolved surfactant molecules. Moreover, they separate as an independent macrophase, which leads to a decrease in the number of surfactant molecules involved in the flotation process.